Study of simply connected domain and its geometric properties. Issue 1 (11th December 2019) - Faisal, M. I.
ABSTRACT: By using composition of a differential operator and a subclass of analytic functions, we introduce a new application of a differential operator for starlike and convex functions. Moreover, we are dealing with starlikeness and convexity properties of hypergeometric and related functions.